Rotation of the pinned direction in artificial antiferromagnetic tunnel junctions by field annealing - Jun, KI; Lee, JH; Shin, KH; Rhie, K; Lee, BC (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2004)
The effect of field annealing on the magnetic tunnel junctions (MTJs) with an artificial antiferromagnetic layer is investigated. Samples, which were grown under the same condition, are annealed with low (200-Oe) and high (1-kOe) magnetic fields. The rotation of the pinned direction is observed for the sample annealed at high magnetic field without decrease of tunneling magnetoresistance by varying the applied field direction. This result provides a method to adjust the pinned direction of the MTJ, which may be critical in switching a magnetic RAM (MRAM) cell.